2017
DOI: 10.1627/jpi.60.1
|View full text |Cite
|
Sign up to set email alerts
|

Supported Metal Catalysts for Total Hydrogenation of Furfural and 5-Hydroxymethylfurfural

Abstract: Total hydrogenation of furfural and 5-hydroxymethylfurfural (HMF), both of which are important platform chemicals from biomass, produces tetrahydrofurfuryl alcohol (THFA) and 2,5-bis(hydroxymethyl)tetrahydrofuran (BHTHF), respectively, and these products can be used as solvent or raw material of resin. Ni catalysts can give good yields in these reactions; however the low activity and stability are problems. Supported monometallic Pd and Ru catalysts have been reported to be also active in hydrogenation, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 54 publications
1
26
0
1
Order By: Relevance
“…Various preeminent reviews have appeared in recent years on the production, upgradation and applications of different biomass‐derived compounds including furans . For instance, Wang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various preeminent reviews have appeared in recent years on the production, upgradation and applications of different biomass‐derived compounds including furans . For instance, Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Various preeminent reviewsh ave appeared in recent years on the production,u pgradation and applicationso fd ifferent biomass-derived compounds including furans. [1,3,31,[35][36][37][38][39][40][41][42][43] For instance,W ang et al re-evaluated hydrotreating and hydrodeoxygenation of bio-oils and their different oxygen-containing compounds such as furans overn on-sulfide metal catalysts. [1] In the same direction, the catalytic upgradation of biomass-derived compoundso ver magnetic catalysts was extensively reviewedb yL iu et al [3] Furthermore, Nakagawa et al described catalytic hydrogenation of furanicc ompounds over several heterogeneous catalysts in the presence of hydrogen gas, [31] while Zhang et al reviewed various catalytic processes for the production of FDCA and its derivatives from HMF.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of 1,2,6-hexanetriol (HT) leads to one-spot or sequential liquid phase [25][26][27]41,42] hydrogenation and ring-opening reactions via hydrogenolysis using mainly batch reactors [26,27,41,42]. Considering this, C=O, C=C and C-O (belonging to furan-ring) bonds cleavage is desirable for the HT production.…”
Section: 26-hexanetriol (Ht) Production Through Catalytic Conversimentioning
confidence: 99%
“…New research reported in the literature is based on the ring-opening of HMF and FF to produce aliphatic or linear polyols (sugar alcohols) [23][24][25] for the chemical industry [26] by means of hydrogenation processes. Among these products, whose general formula is C n H 2n+2 O n , the most investigated alcohols are diols and triols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation